2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path732>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the interleukin-8 receptors, CXCR1 and CXCR2, in inflamed gut tissue

Abstract: There is increasing evidence to suggest that the potent neutrophil chemoattractant interleukin-8 (IL-8) has an important role in the pathogenesis of inflammatory bowel disease. IL-8 mediates its actions via two cell surface receptors, CXCR1 and CXCR2. This paper describes the distribution of these IL-8 receptors in the normal gastrointestinal tract and how this is modified in ulcerative colitis (UC). Paraffin-embedded colonic resection specimens were stained with monoclonal antibodies directed against CXCR1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…In fact, IL-8 increase has been observed in inflamed intestinal mucosa of patients with chronic IBD, implying an important role in the pathogenesis of IBD (Daig et al, 1996;Williams et al, 2000). In agreement with previous reports for IL-8 induction (Murayama et al, 1997;Brasier et al, 1998), our result also demonstrated that IL-8 expression was barely detectable in vehicle-treated HT29 cells or rat colon tissue, and TNBS (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, IL-8 increase has been observed in inflamed intestinal mucosa of patients with chronic IBD, implying an important role in the pathogenesis of IBD (Daig et al, 1996;Williams et al, 2000). In agreement with previous reports for IL-8 induction (Murayama et al, 1997;Brasier et al, 1998), our result also demonstrated that IL-8 expression was barely detectable in vehicle-treated HT29 cells or rat colon tissue, and TNBS (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Williams et al (53) have reported the presence of these two receptors in normal GI tract and also about their modification in inflamed gut tissue. They observed that CXCR1 are strongly upregulated in the mucosal epithelium, specifically and commonly on morphologically damaged surface epithelium (53), whereas the role and distribution of CXCR2 in GI tract has not been well explored.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented in literature that cytokines are involved in the dysregulated inflammatory response in IBD, although the exact mechanism is still unknown. Different studies have reported that IL-8 (mouse homologue is Kc), which is a potent cytokine for recruitment and activation of neutrophils and plays an active role in the induction and promotion of IBD (16,32,34,49,52,53), although none of these studies could delineate the exact mechanism by which IL-8 mediates or propagates inflammation in IBD. Furthermore, Singer and Sansonetti (46) demonstrated that intraluminal addition of recombinant IL-8 was directly associated with the development of acute invasive Shigella-induced colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When IL‐8 combines with CXCR1/2, CXCR1/2 transduces signals via G‐protein coupled receptors (Han, Feng, Chen, Gerard, & Boisvert, ). CXCR1 and CXCR2 are primarily expressed on the surfaces of T cells, monocytes, monocytoid B cells, melanoma cells, synovial fibroblasts, neutrophils, and myeloid progenitor cells (Williams et al., ). During acute inflammation, chemokines interact with the glycosaminoglycans on the surfaces of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%